Conceptual project of the NSC KIPT nuclear physics complex for basic and applied research in the field of nuclear physics, high energy physics and interaction of radiation with substance - Shul’ga, M.F.; Kovalenko, G.D.; Guk, I.S.; Gladkikh, P.I.; Peev, F.A. (Problems of Atomic Science and Technology, 2022)
The main ideas for creating a project for an accelerator complex with an energy of up to 550 MeV with a continuous electron beam for work in high energy physics and nuclear physics are presented. Schematic solutions for injectors, high-frequency system of the complex and magnetic elements are chosen. The choice of the magneto-optical scheme of the recirculator is substantiated. The dynamics of the beam in the facility and the parameters of the extracted beam are studied.